Outras dimensões em saúde: o lugar da arte - Zawadzki, Guilherme (2022)
Introduction: Artistic activities are strategies capable of generating processes of observation of an aesthetic object and, consequently, ethical operations. This premise guided the analysis of the workshop held as part of a vehicle for symbolic constructions of reality to express meanings and senses inherent to the creation process and, in this way, affirm forces of development and, therefore, of health promotion. Objective: to report the experience of the “Oficina Eu Vejo Assim,” which used art as a strategy to promote the well-being of hospitalized children. Method: This is a documentary and qualitative research that started with an experience report of the workshop, in which the child produced a drawing based on the slogan “What is your dream?” and then, this drawing was transformed into a backdrop and produced a photograph. Results: The material obtained had its content analyzed and then organized into categories: subject in perspective; manifest conflicts and outcomes. In general, themes were considered in which children project themselves into heroic and courageous figures and situations, possibly to face the conditions of suffering triggered by the context of hospitalization. Conclusion: the study demonstrated the inherent potential of artistic activities as producers of an object of observation and, consequently, of an aesthetic object based on its internal reality. The analysis of artistic production was also verified as an announcer of emotions and the stories were analyzed to generate a description of a structure with characteristics that develop potentials and the possible reasons for delay in this issue.(AU)